Taking Sinology Classics as the Carrier to Improve Students’ Humanistic Literacy - Lei, J; Xu, M (KnE Social Sciences, 2018)
As the carrier of Chinese traditional culture, classics of sinology bear a long history and rich humanistic spirit, having a positive effect on the education of students from vocational school. At the moment, the work of the vocational school has been highly employment-oriented, and it’s easy to cause the phenomenon of ‘value major and despise humanity’, with the level of humanistic literacy of the students in vocational school not being high. Consequently, it is particularly important to enhance students’ humanistic literacy through the development of Sinology classics teaching in vocational school. Keywords: classics of sinology, vocational education, humanistic literacy